Scenario Planning Implementation : A Case of a Malaysian Organisation - Lim, Lee Chin (2007)
In this dynamic and ever changing era, uncertainties are inevitable. A successful organisation is one that is able to address the uncertainties in a world that is complex and unpredictable. Scenario planning is a strategic management tool that offers an alternative approach to planning in a world where linear logic does not prevail (Geons, 2001). It is a method for learning about the future by understanding the uncertainties and driving forces affecting an organisation’s future. Its core benefits are to facilitate an informed decision making and to enhance organisation learning. Despite its obvious benefits, scenario planning is not widely adopted (Verity, 2003). The methodological confusion and lack of wellestablished and defined implementation process could have contributed to its lack of popularity.This case-study sought to examine the possibility of adopting scenario planning in a Malaysian company, Trojan Berhad’s (not its real name) strategic management process. The approach proposed was based on a study of the current strategic development practices in the said company as well as scenario planning procedures described by van der Heijden, et al (2002). It is hoped that the findings of this study will lead to a better understanding of scenario planning and its adoption in local strategy development practices. The selection of the case for this study was opportunistic as well as one of convenience. I have chosen the company where I worked as the case to study as this proffered a number of advantages which would not be available had I chosen an unrelated company to investigate. The data collection methods used in this study are semi-structured interviews, participant observation and analysis of relevant documents in the subject organisation. This study identified a number of positive aspects underlying Trojan’s current strategic management process that facilitate the adoption of scenario planning process. The organisation’s current strategic management process required minimal adjustment and modification to accommodate scenario planning.Furthermore, adopting scenario planning may be regarded as an extension to what is currently being practised as there is evidence of scenario planning-like procedures in Trojan’s strategic management process. This would help to minimise resistance to the introduction of new concept, i.e. scenario planning. Last but not least, the receptiveness shown by all the respondents who would be directly involved in scenario planning - should it be introduced - would mean that the notion of scenario planning would not be too difficult to introduce to the other levels in the organisation. However, Trojan’s management would still need to address issues such as acculturation of scenario planning process, selection and management of the process and participants in the process, capacity-building for scenario planning, management of scenario development and, last but not least, integration of scenario planning process in existing strategic management processes.minimal adjustment and modification to accommodate scenario planning.Furthermore, adopting scenario planning may be regarded as an extension to what is currently being practised as there is evidence of scenario planning-like procedures in Trojan’s strategic management process. This would help to minimise resistance to the introduction of new concept, i.e. scenario planning. Last but not least, the receptiveness shown by all the respondents who would be directly involved in scenario planning - should it be introduced - would mean that the notion of scenario planning would not be too difficult to introduce to the other levels in the organisation. However, Trojan’s management would still need to address issues such as acculturation of scenario planning process, selection and management of the process and participants in the process, capacity-building for scenario planning, management of scenario development and, last but not least, integration of scenario planning process in existing strategic management processes.